IMMUNOHISTOCHEMICAL STUDY OF PTEN EXPRESSION IN VARIOUS LESIONS OF ATHEROSCLEROSIS - SARAVANAN E,; ANU PRIYADHARSHINI S,; RAMA GOPALAN, (International Journal of Pharma and Bio Sciences, 2014)
Atherosclerosis is one of the major causes of ischaemic heart disease which in turn leads to millions of deaths annually throughout the world. Several theories have been proposed to explain the process of atherogenesis and plaque formation. Molecular mechanisms are recently gaining importance and particularly the role of PTEN is being studied widely. In this study, we evaluated the expression of PTEN by immuno histochemistry in the various atherosclerotic lesions to elucidate the possible role of PTEN in the pathogenesis of the disease. Immuno histochemistry for PTEN showed varied results in the different types of atherosclerotic lesions and the different grades of the disease. We have also analyzed the previous studies extensively and proposed future areas of research in this aspect.